Transformed library spaces lead to transformed library services: a case study of the RCSI library (Journal of EAHIL, 2020)
A new health sciences library integrated into a state of the art academic and clinical education building provided opportunities for transforming library services delivery, positioning space as a service, deeper integration of library expertise within the University community and the curriculum, and for enhancing the student experience.